An exosome-based nanoplatform for siRNA delivery combined with starvation therapy promotes tumor cell death through autophagy, overcoming refractory KRAS-mutated tumors and restoring cetuximab chemosensitivity - Yurong Xiang; Qiang Liu; Kang Liu; Liuxian Chen; Fengjiao Chen; Tao Li; Siqi Li; Qiang Yu; Quan Lv; Zheng Xiang (Materials Today Bio)
Multi-drug combination therapy is one of the most effective strategies for the treatment of drug-resistant and advanced tumors. Modern nanodrug delivery systems are crucial for multi-drug combination therapy and gene therapy. However, research on direct injection of RNAi has not yielded significant results. Artificial vectors are emerging as promising delivery systemts for RNA for gene therapy. In this study, a multi-drug therapy system was built based on a biodegradable exosome nano-platform exploiting the protective and low immunogenic properties of exosomes for RNA. This work aimed to accomplish the co-delivery of siRNA and 3-Bromopyruvic acid (3BP) on an exosome nanoplatform, enhancing targeting by coupling cetuximab (CTX) to exosome membranes, resulting in a new nanomedicine Exo@siRNA/3BP-CTX (ERBC) engineered exosomes. The synthesis conditions were optimized to obtain stable, safe, and effective nanomedicines. Successful targeting of tumors with CTX inhibited KRAS oncogene expression and significantly reduced glucose uptake by cancer cells. This enhanced the starvation therapy effect of the energy deprivation agent 3BP, thus promoting excessive autophagy activation in cells and doubling apoptosis. However, ERBC combined with CTX therapy restored cellular chemosensitivity to CTX. These findings indicate that engineered exosomes with dual therapeutic activities is a promising approach for treating refractory KRAS-mutant cancers.